Homogenization of layered media: Intrinsic and extrinsic symmetry breaking. (4th March 2021) - Tsukerman, Igor; Shahriyar Hossain, A. N. M.; Chong, Y. D.
Abstract: A general homogenization procedure for periodic electromagnetic structures, when applied to layered media with asymmetric lattice cells, yields an effective tensor with magnetoelectric coupling. Accurate results for transmission and reflection are obtained even in cases where classical effective medium theory breaks down. Magnetoelectric coupling accounts for symmetry breaking in reflection and transmission when a non-symmetric structure is illuminated from two opposite sides.